The Terms of Concept, Notion, Frame and Gestalt in Linguistics - Shohkadam Haydarov (International Journal on Integrated Education, 2022)
This article discusses the term concept and its different interpretations in world linguistics, the understanding of this term in conceptual studies, the main concepts of the concept are more often observed in linguocognitology and linguocultural studies, the concept of language is considered a branch of the concept and the conceptosphere it includes.